Serological responses in dairy calves to various vaccines administered via needle-free or conventional needle-based injections - Larry C. Hollis; John F. Smith; B.J Johnson; Sanjay Kapil (Kansas Agricultural Experiment Station Research Reports, 2005)
One hundred and four, 5- to 10-month-old Holstein heifers and steers were blocked by age within gender and randomly assigned to treatments. Calves were vaccinated with 5- way modified-live respiratory viral vaccine, Mannheimia hemolytic bacterin/toxoid, and 5- way Leptospira bacterin, administered via either needle-free or conventional needle-andsyringe injection techniques. Blood samples were collected from all calves at the time of vaccination and 21 days later. Blood sera were analyzed for antibody titers to infectious bovine rhinotracheitis (IBR) virus as the indicator of serological response to the 5-way viral vaccine, to Leptospira pomona (LP) as the indicator of serological response to the 5-way Leptospira bacterin, and to Mannheimia hemolytica (MH) leukotoxoid. Responses of heifers on day 21 to the IBR fraction of the 5-way viral vaccine, MH bacterin, and LP fraction of the 5-way Lepto bacterin did not differ between methods of administration. Responses of steers on day 21 to the IBR fraction of the 5-way viral vaccine and MH bacterin were greater for the needle-free method of administration, whereas serological response to the LP fraction did not differ between methods of administration. We conclude that needle-free injections can eliminate broken needles in the carcass, reduce needle-borne transmission of disease, and possibly produce greater serological responses to various antigens, compared with those obtained with conventional needle-and-syringe injection systems.; Dairy Day, 2005, Kansas State University, Manhattan, KS, 2005; Dairy Research, 2005 is known as Dairy Day, 2005
Keywords: Dairy Day; 2005; Kansas Agricultural Experiment Station contribution; no. 06-46-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 963; Dairy; Dairy calves; Needle-free injections; Vaccines; Serology